Monster Pedagogy: Sources and Strategies for Unleashing Yōkai in Your Classroom - Mindy Landeck (Education About Asia, 2026)
For some time now, Japanese monsters have been enjoying a moment in the spotlight. Yōkai, the supernatural “monsters” drawn from traditional folklore and given material form by early modern visual artists, dominate much of the public face of Japanese popular culture in recent years. The international Pokémon craze of the early aughts has extended more recently to the popularity of Gotōge Koyoharu’s Demon Slayer manga series and the newest iteration of the venerable Godzilla franchise (Takashi Yamazaki’s Godzilla Minus One, 2023). A search of the term “yōkai” in one’s Amazon search bar will reveal that Japan’s mythical creatures have never been a more appealing global commodity. More than simply the denizens of the Japanese collective imagination, yōkai have come to function as recognizable cultural avatars responding to historical moments such as the COVID-19 pandemic or reflecting broad social shifts such as the disintegration of the nuclear family and the looming threats of climate change. This resource article will explore the wealth of pedagogical opportunities that yōkai content offers to educators and offer a compelling rationale for introducing these materials to students at the secondary and undergraduate levels. Suggested models for individual assignments, group projects and immersive classroom activities designed to engage students in gaining a deeper understanding of Japan’s cultural values will be augmented with a resource list of classroom-friendly literature, films, podcasts and other materials.
Keywords: Japan; Monsters; Yokai; Godzilla; Demon Slayer; Pokémon